Menentukan Proporsi Campuran Mortar yang Tepat dengan Pemanfaatan Limbah Fly Ash dan Bottom Ash Ditinjau dari Kuat Tekan - Yayan Adi Saputro; Decky Rochmanto; Wahyu Setyo Darmoko; Muhrodi Muhrodi; Khotibul Umam (Kadiri University, 2022)
The increase in the amount of fly ash and bottom ash waste every year requires proper management and utilization. In the manufacture of concrete, the use of fly ash and bottom ash can be used as a substitute material. However, it has not been utilized in making species in construction. This is because the exact proportion has not been obtained. The purpose of this study was to determine the correct proportions in the mortar with a mixture of fly ash and bottom ash. The research was carried out using experimental methods in the laboratory with cube-shaped specimens (5 x 5 x 5 cm) with 2 kinds of ratios between binder and fine aggregate, namely 1:2 and 1:4, each having a different percentage of sand and bottom ash, starting from from 20% to 80%. While the fly ash used is 10%. Tests carried out included material tests (Metal Oxidation Concentration Test and Sieve Analysis), and compressive strength tests (14 and 28 days). The results showed that the highest mortar compressive strength was at a ratio of 1:2 with fly ash as a cement mixture of 10% and bottom ash as a sand mixture of 20% with a compressive strength value of 16.8 MPa at the age of the specimen 28 days. The compressive strength value is in accordance with the provisions of SNI 03-6825-2002. The results of this study can be used by the community in making plaster work and can reduce the amount of waste that exists today.